Alginate gels crosslinked with chitosan oligomers – a systematic investigation into alginate block structure and chitosan oligomer interaction. Issue 23 (13th April 2021) - Kopplin, Georg; Lervik, Anders; Draget, Kurt I.; Aachmann, Finn L.
Abstract : Three alginates with different block structures, poly-M, poly-G, and poly-MG, were investigated upon ionic crosslinking with chitosan oligomers, using circular dichroism, rheology, and simulations, revealing a unique high gel strength poly-MG chitosan gelling system. Abstract : Three alginates with fundamentally different block structures, poly-M, poly-G, and poly-MG, have been investigated upon ionic crosslinking with chitosan oligosaccharides (CHOS), using circular dichroism (CD), rheology, and computer simulations, supporting the previously proposed gelling principle of poly-M forming zipper-like junction zones with chitosan (match in charge distance along the two polyelectrolytes) and revealing a unique high gel strength poly-MG chitosan gelling system. CD spectroscopy revealed an increased chiroptical activity exclusively for the poly-M chitosan gelling system, indicative of induced conformational changes and higher ordered structures. Rheological measurement revealed gel strengths ( G ′ < 900 Pa) for poly-MG (1%) CHOS (0.3%) hydrogels, magnitudes of order greater than displayed by its poly-M analogue. Furthermore, the ionically crosslinked poly-MG chitosan hydrogel increased in gel strength upon the addition of salt ( G ′ < 1600 at 50 mM NaCl), suggesting a stabilization of the junction zones through hydrophobic interactions and/or a phase separation. Molecular dynamics simulations have been used to further investigate these findings, comparing interaction energies, charge distances and chain alignments. These alginates are displaying high gel strengths, are known to be fully biocompatible and have revealed a broad range of tolerance to salt concentrations present in biological systems, proving high relevance for biomedical applications.